A Cross-Sectional Study on The Levels of Smartphone Use Among Children During The COVID 19 Lockdown in Tamilnadu, India - P, Bijulakshmi; Rajendhiran, Gopi; Ramasubramanian, Vikhram; Kannan, M. (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
Smartphones have made the internet available at our fingertips. More children around the world are born mobile, especially kids born after 2015 (Gen Alpha). This naturally raises questions about the overuse and addictive use of smartphones, which can be counterproductive to their development. The COVID induced lockdown has robbed children of other means of entertainment and combined with the easy access to smartphones due to the online classes, the overuse of smartphones is a concept of great concern to parents. An online survey was conducted in India among parents about smartphone children. The pa parents also filled out a self-constructed questionnaire to find the levels of smartphone addiction in their children. One thousand three hundred thirty people participated in the study, and their responses were used to analyze the various factors contributing to smartphone overuse. The amount of time spent on smartphones has increased exponentially during the COVID-19-induced lockdown, with 14.7% of children spending 5 - 6 hrs per day and a small percentage of children (3.3%) paying more than 9 hrs per day. Children who own a smartphone and adolescent children have higher scores on the smartphone addiction scale. Parents are worried about the increased amount of time spent on smartphones by children of all ages and their inability to regulate it due to the lockdown-induced restrictions. They are particularly concerned about its long-term effects on their children’s physical, social, and psychological health.